Clinical Trials of Silver Diamine Fluoride in Arresting Caries among Children: A Systematic Review. (October 2016) - Gao, S.S.; Zhao, I.S.; Hiraishi, N.; Duangthip, D.; Mei, M.L.; Lo, E.C.M.; Chu, C.H.
This review aims to investigate the clinical effectiveness of silver diamine fluoride (SDF) in arresting dental caries among children. A systematic search of publications was conducted with the key words "silver diamine fluoride, " "silver diammine fluoride, " "silver fluoride, " "diamine silver fluoride, " or "diammine silver fluoride" as well as their translation in Chinese, Japanese, Portuguese, and Spanish in 7 databases: PubMed (English), Embase (English), Scopus (English), China National Knowledge Infrastructure (Chinese), Ichushi-web (Japanese), Biblioteca Virtual em Saude (Portuguese), and Biblioteca Virtual en Salud Espana (Spanish). Duplicated publications were deleted. The title and abstract were screened and irrelevant publications were excluded. The full text of the remaining publications was retrieved. Prospective clinical studies of SDF that reported a caries-arresting effect among children were included. Meta-analysis was performed for quantitative analysis. A total of 1, 123 publications were found, including 19 publications of clinical trials. Sixteen clinical trials studied the caries-arresting effect on primary teeth, and 3 clinical trials were on permanent teeth. Fourteen studies used 38% SDF, 3 used 30% SDF, and 2 used 10% SDF. Meta-analysis was performed on extracted data from 8 studies using 38% SDF to arrest caries in primary teeth. The overall percentage of active caries that became arrested was 81% (95% confidence interval, 68% to 89%;P < 0.001). Apart from staining the arrested lesion black, no significant complication of SDF use among children was reported. SDF was commonly used at 38%. It was effective in arresting dentine caries in primary teeth among children. Knowledge Transfer Statement: This systematic review found that 38% silver diamine fluoride (SDF) can effectively arrest caries among children. SDF treatment is noninvasive and easily operated. It can be a promising strategy to manage dental caries in young children or those who have special needs.